Research on the Innovative Design of "Pan Wang Seal" Pattern of Yao Nationality in Northern Guangdong - Guan, Huilin; Wang, Lizhi (Transactions on Social Science, Education and Humanities Research, 2024)
As one of the national intangible cultural heritages, "Panwang Seal" pattern is a typical symbol of Yao nationality. It has various forms, bright colors and profound cultural connotation. It has special decorative significance and high research value. It is of great significance to persist, develop and carry forward the excellent traditional culture of Yao nationality by deeply exploring the connotation and style characteristics of Yao nationality's "Panwang seal" pattern in northern Guangdong. "Panwang Seal" pattern provides rich materials and inspiration for modern pattern design, and researches and develops the patterns of Yao nationality in northern Guangdong, while protecting and spreading the national culture.